Endoscopic spectrum and practical classification of small bowel gastrointestinal stromal tumors (GISTs) detected during double-balloon enteroscopy - Martinez-Alcalá, Alvaro; Fry, Lucía C.; Kröner, Thomas; Peter, Shajan; Contreras, Carlo; Mönkemüller, Klaus (Endoscopy International Open, 2021)
Background and study aims Information about the endoscopic characterization of small bowel gastrointestinal tumors (GISTs) is limited. The aim of this case study was to describe the endoscopic spectrum of small bowel GISTs and to present a practical classification.Patients and methods Observational, retrospective, consecutive case series of patients with small bowel GIST.Results A total of 10 small bowel GISTs were found in patients (6 male, 4 female, mean age 52 years, range 28 to 68).). All patients presented with obscure gastrointestinal bleeding (overt, n = 8, occult, n = 2). Most GISTs were present in the proximal or middle small bowel (n = 7). The endoscopic tumor characteristics could be categorized as follows: submucosal round (n = 4), submucosal sessile (n = 2), and invasive/penetrating) (n = 4). The mucosa overlying the tumor was normal (n = 4), grooved (n = 3) or frankly ulcerated (n = 3). Tumor size ranged from 8 mm to 50 mm. Biopsy was negative in all patients with normal mucosa but showed tumor in all patients with ulcerations. Regardless of biopsy results, all patients were sent for surgery. Nine resections were carried out. One patient refused surgery. There were no complications of endoscopy in this cohort.Conclusion Our series shows that GISTs have a wider spectrum of endoscopic characteristics than previously described. The round type with normal overlying mucosa was equally prevalent as the grooved or ulcerated variant. Endoscopists should be aware of this wide spectrum of presentation of small bowel GIST.